Enantioselective formation of cyclopropane spiroindenes from benzofulvenes by phase transfer catalysis. Issue 84 (3rd October 2016) - Donslund, Bjarke S.; Jessen, Nicolaj Inunnguaq; Jakobsen, Joakim Bøgelund; Monleón, Alicia; Nielsen, Rune Pagh; Jørgensen, Karl Anker
Abstract : The enantio - and diastereoselective formation of indenes spirofused to highly substituted cyclopropanes is described. Abstract : The enantio - and diastereoselective formation of indenes spirofused to highly substituted cyclopropanes is described. The application of a new cinchona alkaloid derived ammonium salt in a phase transfer catalysis setup facilitates high selectivity and excellent yields at low catalyst loadings (0.1–1.0 mol%).